High nutrient-use efficiency during early seedling growth in diverse Grevillea species (Proteaceae) - He, Tianhua; Fowler, W.; Causley, C. (Nature Publishing Group, 2015)
Several hypotheses have been proposed to explain the rich floristic diversity in regions characterised by nutrient-impoverished soils; however, none of these hypotheses have been able to explain the rapid diversification over a relatively short evolutionary time period of Grevillea, an Australian plant genus with 452 recognised species/subspecies and only 11 million years of evolutionary history. Here, we hypothesise that the apparent evolutionary success of Grevillea might have been triggered by the highly efficient use of key nutrients. The nutrient content in the seeds and nutrient-use efficiency during early seedling growth of 12 species of Grevillea were compared with those of 24 species of Hakea, a closely related genus. Compared with Hakea, the Grevillea species achieved similar growth rates (root and shoot length) during the early stages of seedling growth but contained only approximately half of the seed nutrient content. We conclude that the high nutrient-use efficiency observed in Grevillea might have provided a selective advantage in nutrient-poor ecosystems during evolution and that this property likely contributed to the evolutionary success in Grevillea.